Administrative Buddhist Method for Modern Public Sector - Khamtho, Phramaha Sriarun; Kenaphoom, Assoc. Prof. Dr. Sanya; Kosolkittiamporn, Assoc. Prof. Dr. Soawalak (Journal for Developing the Social and Community, 2016)
In the present situation Nation needs a knowledgeable executive, honestly, especially in modern government organizations. There is a need for ethical executives. This is a strong hold on what is right, acting with a sense of commitment to strengthen the good. It is the responsibility to bring the organization to success according to the intent of the organization. It also brings harmony among the faculty and personnel in the organization. This article is dedicated to presenting Buddhist management methods for modern government organizations; 1) Buddhist method of planning 2) Buddhist method of organization 3) Buddhist method of personnel management 4) Buddhist method of directorial and 5) Buddhist method of supervise